Treasure Hunting in Virtual Environments Self-Organized Criticality in Searches Amid Uncertainty - Volchenkov, Dimitri; Helbach, Jonathan; Tscherepanow, Marko; Kühnel, Sina (Discontinuity, Nonlinearity, and Complexity, 2026)
Searching experiments conducted in different virtual environments over a gender balanced group of people revealed a gender irrelevant scale-free spread of searching activity on large spatiotemporal scales. The better per- formance of men in virtual environments can be associated with the reg- ularly renewed computer game experience, essentially in games played through a first-person perspective. We suggested a simple self-organized critical model of search, in which the experimentally observed scale-free behavior can be interpreted as a trade-off between the value of exploitation versus exploration amid uncertainty.